The Influence of Leadership, Work Discipline, and Work Environment on Employee Performance through Organizational Commitment at the Ulu Idanote Sub-District Office (Pusat Riset dan Inovasi Nasional, 2026)
Employee performance is a critical determinant of organizational effectiveness and the successful delivery of public services. This study investigates the influence of leadership, work discipline, and work environment on employee performance, with organizational commitment as a mediating factor, at the Ulu Idano’e Subdistrict Office, South Nias Regency. A quantitative research design with a survey approach was employed. The population consisted of all 50 employees of the subdistrict office, selected through total sampling. Data were collected using structured questionnaires, validated for reliability and validity, and analyzed using multiple linear regression and mediation analysis to examine both the direct and indirect effects of the independent variables on employee performance via organizational commitment. The results reveal that leadership, work discipline, and work environment each exert a positive and significant impact on organizational commitment, which in turn positively influences employee performance. Among these, leadership emerged as the most dominant factor, underscoring the critical role of effective leadership in guiding, motivating, and supporting employees. Work discipline and a conducive work environment also significantly enhance organizational commitment, mediating the relationship between these factors and employee performance. Simultaneous analysis indicates that the combination of these independent variables accounts for a substantial proportion of the variance in employee performance, highlighting the importance of a holistic and integrated approach to human resource management in governmental organizations. These findings have practical implications for subdistrict-level human resource management, suggesting that enhancing leadership quality, work discipline, and work environment can strengthen organizational commitment, thereby improving employee productivity and motivation. Furthermore, the study provides a foundation for future research aimed at optimizing the performance of governmental employees in other regional contexts.